FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN KLIEN DIABETES MELITUS DALAM MENGONTROL KADAR GULA DARAH DI KELURAHAN PONDOK JAGUNG TANGERANG SELATAN 2017 - Tati Rohayati; Dewi Anggraini (Jurnal Kesehatan STIKes IMC Bintaro, 2018)
Background: Diabetes Mellitus is a chronic disease, so it requires proper management in controlling blood sugar levels to get normal results and prevent complications. This study aims to determine the factors associated with adherence of diabetes mellitus clients in controlling blood sugar levels in Pondok Jagung Village Tangerang Selatan Year. Research Method: Using descriptive quantitative approach is cross sectional with random sampling technique amounted to 204 respondents. The results showed that there was a relationship between knowledge (PValue = 0,002), information exposure (P-Value = 0,001), family support (P-Value = 0,003), health officer support (PValue = 0,000) melitus in controlling blood sugar levels. Conclusion: Respondents with good knowledge had a chance of 3.4 times to control their blood sugar levels, respondents exposed to information had a 3.7 chance to control their blood sugar levels, family-supported respondents had a 3.2 chance to control their blood sugar levels, and respondents who are supported by health workers 4.4 times chance to control blood sugar levels.